INTRODUCTION TO VOLUME 1 : 2003 - Talha, Khairiah (PLANNING MALAYSIA, 2016)
I had always believed that the Malaysian Institute of Planners (MIP) is capable of producing a journal, which had never been done before. The production of this first issue happened after almost four years of my mooting the idea. It was not because of incapability, but there a change in the organizational structure in the midst of producing and putting together this journal. At last this journal is now in your hands as a result of the hard work and effort put forward by a great team of people, led by Assoc. Professor Dr. Alias Abdullah, the Vice President of the Institute. I thank all of them and urge them to continue and dedicate themselves to the furtherance of planning through the journal. For members of the Institute, I would urge the the journal forms part of your educational and learning medium. Reading is to the mind what exercise is to the body. Therefore, reading the journal is certainly pertinent to improve your knowledge of planning and related issues. Reading is a necessity to stay healthy in the business of planning. The wisest mind has always something to learn and learning does not stop upon graduation from university. TO catch up with new issues and experiences, use this journal as a constant companion and reference. Lastly, I express my hope that the journal continues to be produced at least once a years. I therefore call upon members and non-members, whether from the academic world, public service or those in private practice, to contribute your thoughts on paper. You will learn as much by writing as by reading. Thank you.